Peningkatan Hasil Belajar Matematika Melalui Pembelajaran Penemuan - Wulan Perawati (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
This study aims to determine how the learning process in improving students' mathematics learning outcomes through discovery learning. In addition, this study also aims to determine the improvement of students' mathematics learning outcomes through discovery learning. This research was conducted on the second grade students of MI Ishlahuddiniyyah, Pondok Aren District, Tangerang in the 2012/2013 academic year. The method used in this study was action research developed by Kemmis and Taggart. The data analysis used in this study was carried out in two ways, namely quantitative and qualitative approaches. Quantitative analysis shows that there is an increase in students' mathematics learning outcomes starting from pre-research to cycle I, which is 31.87%. Based on the agreement between the researcher and the collaborators, the success of the action can occur if there is an increase in students' mathematics learning outcomes of at least 20%. In this study, the increase in students' mathematics learning outcomes has succeeded in exceeding 20%, thus the research hypothesis can be accepted. The results showed that the application of discovery learning steps in the mathematics learning process was proven to improve students' mathematics learning outcomes. In this case, the concepts of abstract mathematics subject matter can be better understood by students with direct experience and active involvement of students in the discovery learning process (learning by doing).